Sepsis in mechanically ventilated patients with spinal cord injury: a retrospective analysis - Weiterer, Sebastian; Frick, Sarah; Lichtenstern, Christoph; Hug, Andreas; Uhle, Florian; Weigand, Markus A.; Hundt, Guido; Siegler, Benedikt Hermann (Spinal cord, 2019)
STUDY DESIGN: Retrospective analysis. - OBJECTIVES: Sepsis, one of the most frequent and life-threatening complications on intensive care units (ICUs), is associated with a need for mechanical ventilation (MV) as well as adverse respiratory outcomes in hospitalized individuals. However, it has poorly been investigated in patients with spinal cord injury (SCI); a population at high risk for pulmonary and infectious complications. - SETTING: Spinal Cord Injury Center, Heidelberg University Hospital. - METHODS: Over a 5-year period, 182 individuals with SCI requiring MV during their ICU stay were analyzed. Data assessment included demographics, medical characteristics, focus and causative pathogen of sepsis, length of stay, weaning outcomes, and mortality. - RESULTS: Sepsis was recorded in 28 patients (15%), containing a subgroup of individuals suffering from infectious SCI and co-occurring primary sepsis with Staphylococcus aureus as the predominant microorganism. In most individuals, sepsis was found as secondary complication, which was associated with pulmonary foci, Gram-negative bacteria, and high mortality. More than 80% of individuals with secondary sepsis required induction of MV due to respiratory failure. Furthermore, respiratory failure was found to be independent of sepsis focus, spectrum of causative pathogens, SCI etiology, or severity of injury. Subsequent weaning from the respirator was prolonged in more than 90% with a high proportion of weaning failure. - CONCLUSIONS: Sepsis predominantly occurs as a secondary complication after SCI and is associated with detrimental outcomes. Although the lung is frequently affected as a failing organ, not all sepsis foci are pulmonary. Awareness of both actual sepsis focus and causative pathogen is central to initiate an adequate sepsis treatment.
Published online: 09 November 2018
Gesehen am 04.07.2019